Effectiveness of the Electromagnetic Shock Wave Therapy in the Treatment of Cellulite - Débora Apª O. Modena; Caroline Nogueira da Silva; Talita C. P. Delinocente; Tatiane Bianca de Araújo; Tania Maria de Carvalho; Clovis Grecco; Renata Gomes Moreira; Gisele Campos; José Ricardo de Souza; Renata Michelini Guidi (Hindawi Limited, 2019)
In the past centuries, the human body was undervalued; nowadays, however, it is overvalued, and thus the manifestation of the dissatisfactions regarding the body has been increasing. Most of the time, these dissatisfactions are related to cellulite, which is most common in women. Its treatment is one of the challenges which encourage the development of new therapeutic modalities, among them the shockwave therapy. Objective. To evaluate the efficacy of ESWT in the treatment of cellulite in gluteus and posterior of thigh. Method. This is a prospective and comparative study, in which volunteer women who attended the criteria of inclusion were selected and who were subjected to 10 sessions of ESWT. The following were performed as an evaluation method: anthropometry, perimetry, skin viscoelasticity with the Cutometer®, thickness of hypodermis with diagnostic ultrasound, analysis of the scale of severity of cellulite (CSS), and quality of life by the Celluqol® questionnaire. The evaluations occurred before the first session (baseline), after 6 and 10 sessions, and during a follow-up of 3 months after the last session. The statistical test applied was the ANOVA one-way with post hoc of Tukey (P-value < 0.05). Results. There was significant improvement (P<0.05) for CSS, for the variable referring to gross elasticity and skin deformation ability evaluated in the Cutometer® and improvement of quality of life represented by Celluqol®. The result was maintained particularly in the follow-up of 3 months after the end of the treatment. Conclusion. The results presented demonstrated the effectiveness and safety of ESWT in the treatment of cellulite and in the decrease of the degrees, improvement of the aspect of the skin, and reestablishment of quality of life. This trial is registered with ClinicalTrials: NCT03275259.